Tomato (Lycopersicon esculentum) or lycopene supplementation attenuates ventricular remodeling after myocardial infarction through different mechanistic pathways - Pereira, Bruna L.B. [UNESP]; Reis, Patrícia P. [UNESP]; Severino, Fábio E. [UNESP]; Felix, Tainara F. [UNESP]; Braz, Mariana Gobbo [UNESP]; Nogueira, Flávia R. [UNESP]; Silva, Renata A.C. [UNESP]; Cardoso, Ana C. [UNESP]; Lourenço, Maria A.M. [UNESP]; Figueiredo, Amanda M. [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Azevedo, Paula S. [UNESP]; et al. (Elsevier, 2017)
The objective of this study was to evaluate the influence of tomato or lycopene supplementation on cardiac remodeling after myocardial infarction (MI). Male Wistar rats were assigned to four groups: the sham group (animals that underwent simulated surgery) that received a standard chow (S; n=18), the infarcted group that received a standard chow (MI; n=13), the infarcted group supplemented with lycopene (1 mg of lycopene/kg body weight/day) (MIL; n=16) and the infarcted group supplemented with tomato (MIT; n=16). After 3 months, morphological, functional and biochemical analyses were performed. The groups MIL and MIT showed decreased interstitial fibrosis induced by infarction. Tomato supplementation attenuated the hypertrophy induced by MI. In addition, tomato and lycopene improved diastolic dysfunction evaluated by echocardiographic and isolated heart studies, respectively. The MI group showed higher levels of cardiac TNF-α compared to the MIL and MIT groups. Decreased nuclear factor E2-related factor 2 was measured in the MIL group. Lipid hydroperoxide levels were higher in the infarcted groups; however, the MIT group had a lower concentration than did the MI group [S=223±20.8, MI=298±19.5, MIL=277±26.6, MIT=261±28.8 (nmol/g); n=8; P<.001]. We also examined left ventricle miRNA expression; when compared to the S group, the MIL group uniquely down-regulated the expression of eight miRNAs. No miRNA was found to be up-regulated uniquely in the MIT and MIL groups. In conclusion, tomato or lycopene supplementation attenuated the cardiac remodeling process and improved diastolic function after MI. However, the effect of lycopene and tomato supplementation occurred through different mechanistic pathways.
Keywords: Epigenetics; microRNA; Myocardial infarction; Nutrition; Remodeling